(3eaghe GdhSWjI aj GdbQBf hGdSfI (B/s - (3GdOhQj, bMWGf YHO GdQMef,s 1941- ((3HjQhJ (B:s (3cJGH(B-(3fGTQhf,s, 2017)
(3jJfGhd cJGH (B((3eaghe GdhSWjI aj GdbQBf hGdSfI(B) (3hGdPj bGeg HJCdjag (B((3bMWGf YHO GdQMef GdOhQj(B) (3aj MhGdj (B(64) (3UaMI ef GdbWY GdeJhSW ef EUOGQ cJGH(B-(3fGTQhf, ehVhY (B((3GdhSWjI(B) (3eSJYQVG OQGSI ESdGejI JTQM eaghe GdhSWjI aj GdbQBf GdcQje hGdSfI GdfHhjI GdTQjaI dZI hGUWdGMkG ceG JfGhd JYQja GdZdh hCSHGHg heHGOF GdZdGI hYdGL GdZdh(B.s
(3HHdjhLQGajI (B: (3UaMI (B49-60.s
Keywords: (3GdGYJOGd aj GdMOjKs; (3GdGYJOGd aj GdbQBfs